A metabolic CRISPR-Cas9 screen in Chinese hamster ovary cells identifies glutamine-sensitive genes - Karottki, Karen Julie la Cour; Hefzi, Hooman; Li, Songyuan; Pedersen, Lasse Ebdrup; Spahn, Philipp N.; Joshi, Chintan; Ruckerbauer, David; Bort, Juan A.Hernandez; Thomas, Alex; Lee, Jae Seong; Borth, Nicole; Lee, Gyun Min; et al. (Metabolic Engineering, 2021)
Media and feed optimization have fueled many-fold improvements in mammalian biopharmaceutical production, but genome editing offers an emerging avenue for further enhancing cell metabolism and bioproduction. However, the complexity of metabolism, involving thousands of genes, makes it unclear which engineering strategies will result in desired traits. Here we present a comprehensive pooled CRISPR screen for CHO cell metabolism, including ~16,000 gRNAs against ~2500 metabolic enzymes and regulators. Using this screen, we identified a glutamine response network in CHO cells. Glutamine is particularly important since it is often over-fed to drive increased TCA cycle flux, but toxic ammonia may accumulate. With the screen we found one orphan glutamine-responsive gene with no clear connection to our network. Knockout of this novel and poorly characterized lipase, Abhd11, substantially increased growth in glutamine-free media by altering the regulation of the TCA cycle. Thus, the screen provides an invaluable targeted platform to comprehensively study genes involved in any metabolic trait, and elucidate novel regulators of metabolism.
Keywords: Bio-production; Cell metabolism; Chinese Hamster ovary cells; CHO cell; Glutamine free; Metabolic enzymes; Sensitive genes; TCA cycle; Animals; CHO Cells; Cricetinae; Cricetulus; CRISPR-Cas Systems; Gene Editing; Glutamine; CHO; CRISPR pooled Screen; Glutamine; Metabolism